CIVIC DIGITAL NATIVES: THE ROLE OF SOCIAL MEDIA IN SHAPING TANZANIAN YOUTH PARTICIPATION - Mkumbo, Grace Naima; Kisongo, David Juma (Ayden Journal of Management and Social Sciences, 2024)
Civic participation, encompassing diverse community activities aimed at addressing shared challenges, plays a pivotal role in fostering associative behavior and building a robust civil society (Barrett and Brunton-Smith, 2014). This study delves into the significance of civic participation, with a specific focus on its objective to influence governmental actions on behalf of the civic community (Verba et al., 1978), highlighting its contribution to collective identity, mutual respect, and social responsibility (Gil de Zuniga et al., 2016). The study asserts that engagement in civic activities is fundamental to the democratic process, serving as a cornerstone for collective action. Central to this investigation is the exploration of how youth engagement with social media contributes to their offline civic participation in Tanzania during non-election periods. Recognizing the transformative potential of civic participation, this study aims to unravel the dynamics of youth involvement in both online and offline spheres, elucidating the interplay between social media use and tangible civic actions. The study draws attention to the notion that civic participation not only nurtures a sense of collective identity but also instills mutual respect and social responsibility. As the foundation for collective action, these elements are indispensable for the functioning of a vibrant democracy This research adopts a multidimensional approach, acknowledging the complex interrelationships between online and offline civic realms. By examining the role of social media in shaping youth civic participation during non-election periods, the study contributes to a nuanced understanding of contemporary civic dynamics. Furthermore, it sheds light on the potential of digital platforms to bridge the gap between virtual discourse and tangible collective action.